Beyond one-size-fits-all: managing mental health calls with the integrated Behavioral Emergency Assessment and Response (iBEAR) model - Zaiser, Benni; Staller, Mario S.; Koerner, Swen (Frontiers in Psychology, 2025)
Several countries have committed to improving law enforcement response to behavioral emergencies through mental health crisis response and intervention training as well as by implementing crisis intervention team programs. However, these measures often rely primarily on traditional crisis intervention methods adapted from clinical settings. At the same time, not all behavioral emergencies constitute a mental health crisis and can be responded to with a single generic approach. Psychiatric disorders, intellectual and developmental disabilities, and/or adverse life circumstances can also result in behaviors that are below crisis threshold but still prompt emergency calls. Such presentations reflect maladaptive coping mechanisms rather than a complete loss of coping capacity seen during acute crisis and include, for instance, drug-seeking criminal behaviors in individuals with substance use disorders or self-stimulatory behaviors in individuals with autism spectrum disorder, particularly when such behaviors violate social norms. Crisis intervention alone fails to fully address the complex nature of these incidents. Currently, no existing framework effectively integrates guidelines for first responders to manage both acute crises and maladaptive behaviors that do not stem from a crisis state. To fill this gap, we propose the integrated Behavioral Emergency Assessment and Response (iBEAR) model as a theory-driven framework that equips first responders with evidence-based assessment, decision-making, and response strategies, easy to access while managing potentially dynamic and stressful behavioral emergencies. The model responds to well-documented demand for enhanced training and preparedness in managing behavioral emergencies, while also addressing the increasing burden of such incidents on emergency services.